Factors associated with hospitalization for seasonal influenza in a Japanese nonelderly cohort - Sachiko Ono; Yosuke Ono; Hiroki Matsui; Hideo Yasunaga (BMC, 2016)
Abstract Background Nonelderly patients may require hospitalization if their symptoms of influenza are severe. However, little evidence is available about the risk factors for hospitalization for influenza. Methods We used a multicenter outpatient and inpatient database to obtain patients' characteristics and clinical procedures. We identified patients aged <65 years with a confirmed diagnosis of influenza between October 2013 and December 2014. We used a Cox regression model to identify the risk factors for hospitalization, using a comparison group of individuals with a confirmed diagnosis of influenza but who were not hospitalized. Results Of 88,054 patients diagnosed with influenza, 276 (0.3 %) patients were hospitalized. With reference to patients aged 18-64 years, the hazard ratio (95 % confidence interval) for hospitalization in patients aged <2, 2-4, and 5-17 years was 12.25 (8.37-17.93), 4.56 (3.10-6.72) and 1.45 (1.03-2.05), respectively. Anemia, chronic obstructive pulmonary disease, neurologic disease, and regular steroid use were significantly associated with hospitalization. Hazard ratios were adjusted for age, sex, comorbidities, respiratory co-infection, virus type, and influenza season. Conclusions Our findings suggest that younger age and several comorbidities are associated with higher probability of hospitalization for influenza.